Mexiletine dosing and tolerability in refractory chronic migraine: Insights from post-lidocaine infusion treatment - Lucia Liao; Hsiangkuo Yuan; Dylan Selbst; Emily Casaletto; Jiangang Liao; Clinton G. Lauritsen (Cephalalgia Reports)
Background Mexiletine is used as a preventive medication for refractory chronic migraine (rCM) and to prolong migraine improvement following intravenous lidocaine infusion. However, published evidence supporting its use in migraine remains limited. This retrospective study describes the dosing, treatment duration, and adverse effects of mexiletine in a group of patients with rCM following lidocaine infusion. Methods Electronic medical records were reviewed at the Jefferson Headache Center. Baseline pain intensity and monthly headache days were collected at baseline and up to 6 office visits within 1-year post-discharge. The duration of mexiletine treatment was evaluated for up to 40 months post-discharge. Results The study included 329 rCM patients who were prescribed a daily dose of 450 mg. At the last follow-up, the median daily dose was 600 mg (450 mg–750 mg). Mexiletine was discontinued in 36.4% (120/329) of patients due to side effects and in 11.2% (37/329) due to insufficient treatment response. Conclusion In our population, 37% (104/329) remained on mexiletine for over 500 days, indicating a favorable safety profile. While mexiletine can be safely administered in outpatient settings, its use should be reserved for patients with the most refractory cases unless stronger evidence supporting its efficacy in migraine becomes available.